Bahasa Arab dan Sumbangsihnya dalam Pengembangan Bahasa Indonesia: Sejarah, Pengaruh dan Implikasinya - Zarkasi, Muhammad Satria; Amiinulloh Asyari, Emha Hasan; El. Warfali, Sulaiman Hasan Sulaiman; Smeer, Zeid B (Jurusan Pendidikan Bahasa Arab, 2026)
In this study, the researcher discusses the importance of Arabic contribution in expanding Indonesian vocabulary. Arabic has an important role in the history of language and cultural development in Indonesia. This research explains how the interaction between Arabic and Indonesian language has shaped the vocabulary and grammar of Indonesian society. This research uses the literature method by making literature sources and scientific information to find out the traces of Arabic influence on the Indonesian language. The results of this study open a deeper insight into the history of the entry of Arabic into Indonesia and its contribution in enriching the Indonesian language treasury.